Persepsi Masyarakat terhadap Program Makan Siang Gratis Menggunakan Text Network Analysis (TNA) - Aziz, Muhamad Apriliana; Alamanda, Dini Turipanam; Fadhlurrohman, Mochammad Iqbal; Kurniati, Dinar Mariam (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
This study examines public perception of the Free Lunch program in Indonesia using Text Network Analysis (TNA). This research method uses a qualitative approach using the Infranodus platform. The use of Text Network Analysis helps identify key themes, relationships between ideas, and emotional patterns that emerge from audience responses. By analyzing public perception from the YouTube platform, this study found that perceptions of the free lunch program were divided between neutral, positive and negative. The results of the analysis through the Infranodus platform show that the majority of people on the media stated that they were neutral towards this program, namely 78%, with positive sentiment of 16% coming from social and health benefits, while negative sentiment of 6% was related to concerns about implementation and transparency. The majority of people in the comments column stated that they were neutral towards this program, namely 76%, with positive sentiment of 13% coming from the fields of direct benefits, social, education and health. While negative sentiment of 11% was related to concerns about the sustainability of the program and potential problems in its implementation. The results of this study are expected to help open insights in improving communication and strict monitoring for efficient and effective implementation.